Penentuan Sampling Audit Menggunkan Metode Monetary Unit Sampling (MUS) pada Akun Beban Operasional PT ABC oleh KAP EFG - Ria Rismawati; Nurmala Nurmala; Maryani Maryani (Jurnal Ilmiah ESAI, 2021)
This study aims to find out how to determine audit sampling conducted by KAP EFG & Partners on PT ABC's 2019 income statement, especially on the operating expense account. One of the procedures implemented by the auditor is conducting a Test Of Detail (TOD), the steps used by the auditor to carry out the procedure are audit sampling using the monetary unit sampling method. The data collection method used in the preparation of this final project is a documentation method in the form of financial reports, general ledger, and journal vouchers. The data analysis method used is a quantitative method. Based on the results and discussion, the authors conclude that there are 6 items that can be sampled with the number of each item being 1 transaction with an interval of Rp. 218,963.943.